PENGARUH AGROFORESTRI TERHADAP KUALITAS DAERAH ALIRAN SUNGAI CILIWUNG HULU, JAWA BARAT (Impact of agroforestry on the quality of Ciliwung Hulu Watershed, West Java) - Rini - Fitri; Adisti Permatasari Putri Hartoyo; Nur Intan Simangunsong; Halus Satriawan (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2020)
ABSTRACTWatershed ecosystem will be stable when the relationship between the components of watershed are stable. Ecological and biophysical disturbances in watersheds are closely related to the disruption of its ecosystem components.The research was conducted to analyse the contribution of agroforestry system to the quality of watershed management, such as erosion, curve number (CN), and potential air retention. This study used qualitative method with steps survey, observation and interviewed the respondents who have the land and joint in the study site to obtain agroforestry practice data, vegetation components, and biophysic condition. Erosion prediction used the Universal Soil Loss Equation (USLE) equation, analyzis of the CN used an empirical equation to estimate surface run-off as a result of the rainfall, land cover changes, and soil hydrological groups (Cover complex classification). The value of a CN was based on the maps of soil types and land cover, the potential retention value (S), the value curve, and the rainfall factor (P). The results showed that the types of agroforestry affected the quality of watershed landscape management with indicators were erosion, curve numbers and potential air retention. Those indicators have a quantitative relationship with various types of agroforestry. The value of soil hydrological group (KHT) in the agroforestry types of Ciliwung Hulu Watershed in West Java Province was dominated by KHT B. This value indicated that the infiltration capacity in the current study location was moderate. The amount of CN obtained varies between 44-78. Keywords: agroforestry; curve number; erosion; potential retention; watershed management ABSTRAK Ekosistem Daerah Aliran Sungai (DAS) akan stabil jika hubungan antar komponen DAS stabil. Gangguan ekologis dan biofisik DAS terkait erat dengan terganggunya komponen ekosistemnya. Penelitian ini dilakukan untuk menganalisis keterkaitan hubungan agroforestri dengan kualitas DAS dari segi erosi, CN dan retensi air potensial. Penelitian ini dilakukan melalui tahapan survei lapang dan wawancara responden untuk memperoleh data praktek agroforestri, komponen penyusun tipe agroforestri dan kondisi biofisik. Prediksi erosi menggunakan persamaan Universal Soil Loss Equation (USLE), sedangkan analisis CN menggunakan persamaan empiris untuk memperkiraan aliran permukaan akibat hujan, perubahan tutupan lahan dan kelompok hidrologi tanah. Nilai CN diperoleh berdasarkan peta jenis tanah dan peta tutupan lahan, nilai retensi potensial (S), dan factor curah hujan (P). Hasil penelitian menunjukkan bahwa agroforestri mempengaruhi kualitas pengelolaan lanskap DAS, baik erosi, CN maupun retensi air potensial. Erosi, CN dan retensi air potensial memiliki hubungan kuantitatif dengan berbagai tipe agroforestri. Nilai kelompok hidrologi tanah (KHT) pada tipe agroforestri lanskap DAS Ciliwung Hulu Provinsi Jawa Barat didominasi oleh KHT B. Nilai ini menunjukkan bahwa kapasitas infiltrasi di lokasi penelitian berada pada tingkat sedang. Nilai CN yang didapat bervariasi antara 44 – 78.Kata kunci: agroforestri; curve number; erosi; pengelolaan DAS; retensi potensial